HAMBATAN KOMUNIKASI TERAPEUTIK BIDAN KEPADA IBU HAMIL DALAM UPAYA PENURUNAN ANGKA KEMATIAN IBU (AKI) DI SERANG (STUDI DESKRIPTIF KUALITATIF TENTANG HAMBATAN KOMUNIKASI TERAPEUTIK BIDAN KEPADA IBU HAMIL DI PUSKESMAS TUNJUNG TEJA, KABUPATEN SERANG) - Dhita Prasanti; Ikhsan Fuady (Jurnal Nomosleca, 2016)
AbstractAs a health worker, midwife should have a good therapeutic communication skills, so that he can establish a relationship of trust with the patient, providing professional satisfaction in obstetric care, and improve the image of the profession of midwifery. But the most important is to apply their knowledge to help their fellow human beings. Maternal Mortality Rate (MMR) is one of the indicators that should be considered by the midwife. If the Maternal Mortality Rate (MMR) increases, the solution must be found in order to prevent this AKI. This is why researchers are interested to raise the research on Therapeutic Communication Barriers To Midwives Pregnancy Prevention in Maternal. Mortality Rate (MMR). The purpose of this study is the researcher wanted to know how therapeutic communication barriers between midwives to pregnant women in the prevention of maternal mortality is increasing. Based on data obtained from the Department of Health, the maternal mortality is very high in Serang district. Therefore, in this study, the researchers raised the case of therapeutic communication barriers midwives to pregnant women in the district of Serang. In this study, researcher used a qualitative approach with descriptive methods. The data collection techniques are observation, interviews, and documentation study. The theory of communication shall be used to analyze this research is the theory of symbolic interaction. Results of research have shown that therapeutic communication barriers that occur between midwives to pregnant women in Puskesmas Tunjung Teja Serang Regency is a semantic barriers (language), cultural barriers, and psychological barriers.DOI : https://doi.org/10.26905/nomosleca.v2i2.606